Bridging factorial and gradient concepts of resource co‐limitation: towards a general framework applied to consumers. (20th December 2015) - Sperfeld, Erik; Raubenheimer, David; Wacker, Alexander
Abstract: Organism growth can be limited either by a single resource or by multiple resources simultaneously (co‐limitation). Efforts to characterise co‐limitation have generated two influential approaches. One approach uses limitation scenarios of factorial growth assays to distinguish specific types of co‐limitation; the other uses growth responses spanned over a continuous, multi‐dimensional resource space to characterise different types of response surfaces. Both approaches have been useful in investigating particular aspects of co‐limitation, but a synthesis is needed to stimulate development of this recent research area. We address this gap by integrating the two approaches, thereby presenting a more general framework of co‐limitation. We found that various factorial (co‐)limitation scenarios can emerge in different response surface types based on continuous availabilities of essential or substitutable resources. We tested our conceptual co‐limitation framework on data sets of published and unpublished studies examining the limitation of two herbivorous consumers in a two‐dimensional resource space. The experimental data corroborate the predictions, suggesting a general applicability of our co‐limitation framework to generalist consumers and potentially also to other organisms. The presented framework might give insight into mechanisms that underlie co‐limitation responses and thus can be a seminal starting point for evaluating co‐limitation patterns in experiments and nature.